Identificação de genes envolvidos na patogênese de Brucella ovis em modelo murino - Teane Milagres Augusto da Silva (2010)
Brucella ovis is one of the main causes of reproductive failure in sheep. Due to the scarcity of studies of B. ovis infection in the mouse, a murine model of infection was developed in this study. BALB/c or C57BL/6 male mice were inoculated intraperitoneally with 106CFU of B. ovis and fragments of the spleen, liver and genital tract were collected for bacteriology, histopathology and immunohistochemistry. Both mice strains had similar kinetics of B. ovis infection and developed microgranulomas in the liver and spleen, with low numbers of intralesional immune-stained B. ovis. There was minimal colonization of genital tract in both mice strains, resulting in mild periorchitis or periepididimytis, indicating that B. ovis does not have a clear tropism for the genital tract in the mouse. However, the mouse is a suitable infection model for B. ovis. Additionally, B. ovis mutant strains were generated by deletion of virB2 gene (nonfunctional T4SS), deletion of putative hemagglutinin or deletion of ORFs encoding an ABC transporter. ABC and virB2 mutant strains were attenuated for colonization in spleen and liver when compared to the wild type (WT) strain (p<0.001) at all time points. However, hemagglutinin had wild type levels of colonization in the spleen and liver, suggesting that putative hemagglutinin gene is not required for B. ovis pathogenesis. Additionally, ABC and virB2 survive less than WT (p<0.01) in peritoneal macrophages and extracellularly in the peritoneal cavity. Moreover, ABC transporter and WT virulence were compared in IRF-1-/- male mice. WT infection was 100% lethal to IRF-1-/- mice until 14 dpi, whereas ABC transporter was not lethal. These results confirm the requirement of specific ABC transporter and T4SS for full virulence and survival in vivo of B. ovis.